2021
DOI: 10.1002/jmv.26938
|View full text |Cite
|
Sign up to set email alerts
|

Severity of RSV infection in Southern European elderly patients during two consecutive winter seasons (2017–2018)

Abstract: In Europe, the respiratory syncytial virus (RSV) surveillance system is very heterogeneous and there is growing evidence of the importance of RSV infections resulting in hospitalization of elderly patients. The aim of this study was to assess the severity of RSV infection in the elderly living in the aged Southern European countries. We conducted a retrospective study of elderly patients ( ≥65‐year old) admitted for laboratory‐confirmed RSV infection in three tertiary hospitals in Portugal, Italy, and Cyprus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Our estimates, based on the available data, suggest a high burden of RSV in terms of hospital admissions in adult populations. Several studies have previously reported the burden and severity of clinical outcomes of RSV among adults in different settings [7,9,10,[27][28][29][30]. For instance, in previous studies, the prevalence of RSV has been reported to be two times higher in patients aged over 75 years compared to those aged below 60 years [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our estimates, based on the available data, suggest a high burden of RSV in terms of hospital admissions in adult populations. Several studies have previously reported the burden and severity of clinical outcomes of RSV among adults in different settings [7,9,10,[27][28][29][30]. For instance, in previous studies, the prevalence of RSV has been reported to be two times higher in patients aged over 75 years compared to those aged below 60 years [31].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is becoming increasingly clear that RSV is not only a pediatric disease but also the cause of severe respiratory infections in the elderly, often leading to intensive care admission and even death. 39,40 Although the data are reliable for the Icelandic population, caused by the small size and strong healthcare infrastructure for children the results may not be representative for other countries.…”
Section: Discussionmentioning
confidence: 90%
“…OSA and OHS also conferred a mortality risk as did solid malignancies. 10 Over the same time frame, Boattini et al also studied hospitalized adults >85 years of age with community-acquired or nosocomial RSV and reported that COPD or asthma were associated with findings of pneumonia in the study population; COPD or asthma, RSV, and influenza B resulted in greater use of NIV. Another stark finding of this study is the reported mortality risk due to CKD.…”
Section: Rsv Disease In Older Adultsmentioning
confidence: 98%